Quantifying micron-scale grain detachment during weathering experiments on limestone. (15th January 2016) - Levenson, Yael; Emmanuel, Simon
Abstract: Weathering in carbonate rocks is often assumed to be governed by chemical dissolution. Nevertheless, chemical processes can be coupled to mechanical mechanisms, with small grains undergoing partial dissolution along grain boundaries, followed by detachment from the rock surface. Crucially, this process can even extend down to the micron-scale. Although chemo-mechanical detachment could be critical for the understanding of carbonate weathering at the global scale, the role it plays has not been directly quantified. To calculate the contribution of grain detachment to surface retreat rates, and to determine the impact of the flow regime, we carried out a series of flow-through weathering experiments on micritic limestone. Using atomic force microscopy, we obtained high resolution in situ data of surface topography for reacting rock surfaces. In all the experiments, both grain detachment and chemical dissolution were observed. Under the laminar flow conditions we explored, we found no clear correlation between flow rate and the size of detached grains, or between the flow rate and the frequency of grain detachment events. Importantly, our results establish that grain detachment contributes significantly to the overall surface retreat, on average accelerating mass loss by 38%. In addition to speeding up weathering, this micron-scale mechanism could also influence the evolution of porosity in aquifers and hydrocarbon reservoirs, and provide a natural flux of colloids that could transport heavy metals or radionuclides in groundwater.